Peran Mahkamah Konstitusi sebagai Lembaga Penguji Undang-Undang dalam Masyarakat Ekonomi ASEAN - Januari Sihotang (Faculty of Law, Maranatha Christian University, 2015)
Constitutional Court is the guardian and single interpreter of the Constitution of 1945. Constitutional Court has authorities to review law against constitution including a law, which based on ratification of a treaty or convention. . Therefore, Constitutional Court has a role to implement and guard constitution of Indonesia in case the implementation of ASEAN Economic Community (AEC) as one main focus of ASEAN Charter could harm constitutional right of citizen and if the AEC is not in line with national goals of Indonesia according to constitution of 1945.